On the bright side : stories about friendship, love, and being true to yourself - Shankle, Melanie (Zondervan, 2020)
"As Melanie Shankle - New York Times bestselling author and founder of the Big Mama blog - opens up with humor and great stories about friendship, love, and what it takes to be true to yourself, you'll be encouraged to find your way again in a world that can make you feel a little bit crazy"--